Institutional and Market Forces in Wage Inequality: A Narrative Review - Cupiadi, Hedi (Indonesian Scientific Publication, 2025)
This study conducts a narrative review to investigate the interplay of institutional and market forces shaping wage inequality in contemporary labor markets. The primary objective is to assess how educational background, gender, informal employment, migration, and labor market regulations contribute to wage disparities across different socioeconomic contexts. A comprehensive literature analysis was employed, reviewing peer-reviewed articles, cross-national studies, and policy documents sourced from major academic databases. The review identifies formal education as a fundamental determinant of upward wage mobility, while acknowledging the growing relevance of non-formal skills in bridging employment gaps. Gender bias continues to influence wage distribution, sustained by institutional inertia and underdeveloped enforcement mechanisms. Informal sector employment and migrant labor status remain critical barriers to equitable wages, largely due to the absence of legal safeguards and systemic exclusion from labor protections. Labor market policies—particularly minimum wage enforcement and social protection mechanisms—have shown varying degrees of effectiveness. Their success is highly contingent on implementation quality and institutional robustness. Interactions between market dynamics and institutional frameworks are pivotal in shaping labor outcomes. The review highlights the need for integrated policy approaches that combine education reform, labor protections, and inclusive economic planning to address the structural roots of wage inequality. Further interdisciplinary research is necessary to inform context-sensitive, long-term solutions.